Pembuatan Pembersih Lantai Alami dengan Ekstraksi Daun Sirih (Piper Betle L.) dan Serai Wangi (Cymbopogon Bernardus L.) terhadap Aktivitas Bakteri - Jaida Tussakinah; Ridwan Ridwan; Nahar Nahar (Jurnal Teknologi, 2026)
This study aims to evaluate the effect of maceration time and composition ratio of betel leaf (Piper betle L.) and lemongrass (Cymbopogon nardus) extracts on the characteristics and antibacterial activity of natural floor cleaners. The extraction method used was maceration with soaking time variations of 2–6 days and extract composition ratios of 1:0, 0:1, 1:1, 1:2, and 2:1. The parameters analyzed included pH, density, organoleptic properties, and antibacterial activity using the colony counter method. The results showed that the pH increased from 5.2 to 7.2 with longer maceration time, while the density remained relatively stable in the range of 0.90–0.93 g/mL. Antibacterial activity also increased with extraction time, with the highest effectiveness observed at 6 days of maceration, achieving a bacterial reduction of 66.41%. Organoleptic evaluation indicated that the product was generally acceptable to panelists, with neutral to favorable responses. The optimal formulation was obtained at 6 days of maceration with a 1:2 ratio of betel leaf to lemongrass extract, producing favorable physicochemical properties and the highest antibacterial activity. This study demonstrates the potential of natural ingredients as eco-friendly and safe alternatives for floor cleaning products.